2009
DOI: 10.5465/amj.2009.41331491
|View full text |Cite
|
Sign up to set email alerts
|

The Role Of Context In Work Team Diversity Research: A Meta-Analytic Review

Abstract: Integrating macro and micro theoretical perspectives, we conducted a meta-analysis examining the role of contextual factors in team diversity research. Using data from 8,757 teams in 39 studies conducted in organizational settings, we examined whether contextual factors at multiple levels, including industry, occupation, and team, influenced the performance outcomes of relations-oriented and task-oriented diversity. The direct effects were very small yet significant, and after we accounted for industry, occupa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

49
981
6
5

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 1,111 publications
(1,041 citation statements)
references
References 111 publications
49
981
6
5
Order By: Relevance
“…Research that crosses levels, for instance, bringing higher levels of analysis to understanding performance at the group level and examining intergroup equality at the more micro-level have received little attention. Research by Joshi and colleagues has taken such a 13 direction, showing that demographic diversity at the occupation-level moderates the effects of group diversity on group-level performance (Joshi & Roh, 2009) and that diversity at the grouplevel influences intergroup equality in the form of reducing earnings inequalities for members of disadvantaged groups (Joshi, Hui & Jackson, 2006).…”
Section: A Positive For What?mentioning
confidence: 99%
See 1 more Smart Citation
“…Research that crosses levels, for instance, bringing higher levels of analysis to understanding performance at the group level and examining intergroup equality at the more micro-level have received little attention. Research by Joshi and colleagues has taken such a 13 direction, showing that demographic diversity at the occupation-level moderates the effects of group diversity on group-level performance (Joshi & Roh, 2009) and that diversity at the grouplevel influences intergroup equality in the form of reducing earnings inequalities for members of disadvantaged groups (Joshi, Hui & Jackson, 2006).…”
Section: A Positive For What?mentioning
confidence: 99%
“…Last, time has been examined as a moderator, particularly in terms of decreasing the negative effects of demographic diversity on group processes (e.g., Pelled et al, 1999; and occasionally in showing the positive effects of demographic diversity over time (Earley & Mosakowski, 2000), but more longitudinal research is still needed. In general, research on the moderating effects of work and task characteristics is very limited (Joshi & Roh, 2009) and only a small fragment of this work emphasizes the positive aspects of diversity for intergroup outcomes, relations or performance.…”
Section: B Positive When?mentioning
confidence: 99%
“…Many Research studies have indicated that since service-oriented industries are involved more frequent and closer interactions with customers, enhancing diversity based on demographic attributes in such industries can actually enhance a firm's "market competence" giving it a competitive advantage in the service industry (Richard et al, 2007). Hence in the service industry, it is expected that greater gender, race or age diversity is likely to have positive rather than negative performance outcomes (Joshi et al, 2009) However, the manufacturing industry is often characterized by a greater reliance on physical capital/equipment and relatively less frequent direct customer-based interactions (Quinn et al, 1996), hence diversity attributes are less likely to directly impact performance in this industry setting (Richard et al, 2007). As compared to these service and manufacturing industries, high-tech industries depend more on intellectual capital and invest relatively more in research and development (OECD, 2006).Thus, based on these views, it can be assumed that task-oriented attributes that can enhance a team's cognitive resource base may have a more significant direct impact on performance outcomes in high tech industries.…”
Section: Industry Setting and Team Diversitymentioning
confidence: 99%
“…A significant part of social research on stereotype formation has specified the psychological processes by which the occupational demography in organizations can influence diversity dynamics within teams Occupational demography (majority-dominated versus balanced) serves as the situational setting that can enhance the effects of relations-oriented diversity and minimize the effects of task-oriented diversity on team performance (Joshi et al,2009) According to (Brewer, 1988), once categorization-based processes are evolved, additional information about targeted group members is filtered out and individuating processes are completely blocked .These categorization-based processes are likely to influence interactions in diverse teams especially when the environment evokes negative stereotypes against certain particular demographic groups, In a recent study, Lepine et al (2002) questioned the relationship between sex and team performance and found that all-male teams (majority dominant vs. balanced) were the worst configuration for performance on a decision-making task (even though it was a masculine-type task). Male teams tended to make decisions that were overly aggressive.…”
Section: Hypothesis 1: Relations Oriented Diversity Is Likely To Havementioning
confidence: 99%
See 1 more Smart Citation